Alternative Methods for Defining Osteoarthritis and the Impact on Estimating Prevalence in a US Population‐Based Survey. Issue 5 (May 2016) - Cisternas, Miriam G.; Murphy, Louise; Sacks, Jeffrey J.; Solomon, Daniel H.; Pasta, David J.; Helmick, Charles G.
Abstract : Objective: Provide a contemporary estimate of osteoarthritis (OA) by comparing the accuracy and prevalence of alternative definitions of OA. Methods: The Medical Expenditure Panel Survey (MEPS) household component (HC) records respondent‐reported medical conditions as open‐ended responses; professional coders translate these responses into International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes for the medical conditions files. Using these codes and other data from the MEPS‐HC medical conditions files, we constructed 3 case definitions of OA and assessed them against medical provider diagnoses of ICD‐9‐CM 715 (osteoarthrosis and allied disorders) in a MEPS subsample. The 3 definitions were 1) strict = ICD‐9‐CM 715; 2) expanded = ICD‐9‐CM 715, 716 (other and unspecified arthropathies) OR 719 (other and unspecified disorders of joint); and 3) probable = strict OR expanded + respondent‐reported prior diagnosis of OA or other arthritis excluding rheumatoid arthritis. Results: Sensitivity and specificity of the 3 definitions, respectively, were 34.6% and 97.5% for strict, 73.8% and 90.5% for expanded, and 62.9% and 93.5% for probable. Conclusion: The strict definition for OA (ICD‐9‐CM 715) excludes many individuals with OA. The probable definition of OA has the optimal combination of sensitivity and specificity relative to the 2 other MEPS‐based definitions and yields a national annual estimate of 30.8 million adults with OA (13.4% of US adult population) for 2008–2011.